Near-infrared Absorbing Probes of Platinum(II) Complexes for Bio-imaging - MASUYA-SUZUKI, Atsuko (BUNSEKI KAGAKU, 2024)
Photoacoustic imaging (PAI) is an imaging technique in which near-infrared light is irradiated onto a biological tissue and the resulting ultrasound waves are converted into an image. The mechanism of optical excitation and ultrasound detection enables high-resolution imaging in depths of several centimeters. When exogenous dyes are accumulated at specific sites as PA probes, it is possible to obtain site-selective images. Recently, target-responsive PA probes have been developed, but there are still few examples of their design. The author has studied the structure-property relationship of platinum(II) diradical complexes that absorb near-infrared light, and reported the behavior of near-infrared light absorption in response to pH and hydrophobic cavity, as well as their mechanisms. Furthermore, the author has found that platinum(II) diradical complexes can be used as photothermal therapeutic agents with high photostability. In this article, PAI and PA probes are explained, and an explanation is given on the progress of research on platinum(II) diradical complexes, which are the subject of our research, then an introduction is proved of research results from one of the author’s studies, a platinum(II) diradical complex as a PA probe with signal-switching and therapeutic functions.